Historia leksykonu "De verborum significatu" - Kuszewska, Katarzyna (Collectanea Philologica, 2014)
The Lexicon of Verrius Flaccus (De verborum significatu) is the first Latin dictionary which included a lot of information about the history, society, religion and topography of Rome. Unfortunately, it is only known in fragments and abridgments. The epitome of this lexicon was created by Pompeius Festus, who probably lived in the second century. His work now exists only in fragments within a single manuscript, the Codex Farnesianus. We can reconstruct this text thanks to Paul the Deacon who also abridged the work of Festus for Charlemagne. Over the years, many editions of the text have been created which consisted of the work of Festus and the epitome of Paul. Today, we have few critical editions and comments on the text. This Lexicon is an amazing source of information and is of great importance to scholars of antiquity.